FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPATUHAN WAJIB PAJAK PASCA PENERAPAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 - Santuo Santuo (Politeknik STIA LAN Makassar, 2020)
Taxpayer compliance is one of the determining factors in achieving tax revenue. The government has made efforts to improve taxpayer compliance. One of the efforts is by issuing Government Regulation Number 23 of 2018. This study aims to determine the effect of the tax rate changes, the application of the principle of tax fairness and tax socialization application on taxpayer compliance in the Bulukumba Tax Office after the implementation of Government Regulation Number 23 of 2018. The number of samples/respondents in this study are 120 taxpayers at Bulukumba Tax Office, which determined by cluster random sampling technique from three districts in the Bulukumba Tax Office Area. This study used questionnaire as data collection instrument. For Data analysis, researcher used multiple linear regression analysis with partial and simultaneous hypothesis tests. The results indicate that tax rates, the principle of tax fairness and tax socialization had a positive and significant effect on taxpayer compliance. This means that taxpayer compliance at Bulukumba Tax Office after the implementation of Government Regulation Number 23 of 2018 generally influenced by the tax rate changes, the application of the principle of tax fairness and tax socialization and the others influenced by other factors not included in this research model